Hydrogen Bond‐Induced Cathode Engineering Enables Binary All‐Small‐Molecule Organic Solar Cells with 15.88% Efficiency and Enhanced Thermostability. Issue 9 (24th July 2022) - Cao, Luye; Du, Xiaoyang; Li, Xinrui; He, Zeyu; Lin, Hui; Zheng, Caijun; Yang, Gang; Chen, Zhenhua; Tao, Silu
Abstract : All‐small‐molecule organic solar cells (ASM‐OSCs) have the advantages of simple structure, easy purification, and small‐batch variation, thus showing broad prospects for commercialization. However, less research has been conducted on the transport layer of ASM‐OSCs, resulting in a low match between the active and transport layers, which limits the increase of the power conversion efficiency (PCE) of the device. Therefore, an electron transport layer (ETL) optimization strategy is proposed to improve device performance by introducing 1, 8‐Octanediol (DOH) into the conventional ETL of PDINN to form intermolecular hydrogen bonds, which can reduce the work function of the electrode and accelerate the electron transport. By depositing the optimized ETL on BTR‐Cl:Y6‐based active layer, the ASM‐OSC achieves a champion PCE of 15.88% with excellent thermostability. Moreover, DOH‐doped PDINN endows the ASM‐OSC with good tolerance to the film thickness of the ETL. When the thickness of the ETLs is increased from 10 to 50 nm, the PCE of the optimized device still maintains at 81.68% of the highest value, demonstrating great potential for large‐area and industrial production. These results suggest that the hydrogen bond‐based interface optimization strategy is a simple and efficient way to enhance the performance of ASM‐OSCs. Abstract : Herein, an optimization strategy of electron transport layer based on hydrogen bond is proposed. 1, 8‐Octanediol (DOH) can form hydrogen bonds with PDINN, which reduces the work function of the electrode and optimizes the carrier transport process, so that the binary all‐small‐molecule organic solar cells obtain a high power conversion efficiency (PCE) of 15.88% with enhanced thermal stability.